Kemampuan Berpikir Aljabaris Siswa SMP dalam Menyelesaikan Soal Matematika Berbasis Etnomatetika - Ayu, Sukma; Yani, Hikmah Fitri; Fadila, Yustia Fikratul; Latifah, Nur Malasari; Purwanti, Nita Lily; Sutrisno, Sutrisno (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Algebraic thinking ability is the ability to connect algebraic concepts with various problems, both in academic contexts and in everyday life. The purpose of this study was to describe junior high school students’ algebraic thinking ability in solving mathematics problems based on ethnomathematics. The study was conducted at a private junior high school in the city of Semarang during the 2025–2026 academic year. This research employed a descriptive qualitative approach. Data were collected through tests, interviews, and documentation. The subjects consisted of three female students categorized based on high, moderate, and low mathematical ability. The results showed that the student with high mathematical ability was able to fulfill all indicators of algebraic thinking ability, the student with moderate mathematical ability fulfilled only four indicators, while the student with low mathematical ability fulfilled only two indicators of algebraic thinking ability.